ANALISIS SISTEM PEMASARAN IKAN WADER (Family Cyprinidae) DI KABUPATEN LAMONGAN - Suyoto, Suyoto; Sa'adah, Wachidatus (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study aims to analyze the marketing channels of wader fish, the marketing system of wader fish, and the marketing efficiency of wader fish in Gondang Lor Village, Sugio District, and the marketing destination area. The research method used a survey method with a research sample of nine wader fish farmers and fishermen in Gondang Lor Village. The data were analyzed using quantitative descriptive analysis. The results showed that the income obtained by fishermen and farmers was Rp. 2,947,000.00 per farmer or fisherman for fresh wader fish and Rp. 2,000,000.00 for fried wader fish. The marketing channel for wader fish in Gondang Lor Village consists of two channels, namely direct channels and indirect channels. Furthermore, the wader fish marketing system, including marketing costs, marketing margins and the largest marketing profits are found in the Pekanbaru Market, namely marketing costs of IDR 1,687.50 / kg, marketing margins of IDR 5,500.00 / kg and marketing profits of IDR 5,812.50 / kg. The results also found that the marketing of wader fish to Lamongan fish market, market in Surabaya, market in Sidoarjo and market in Central Java has been efficient, this is seen from the average farmer's share value of 70% for the four marketing destination areas which is greater than the marketing margin value. Thus, it can be concluded that the marketing of wader fish in Gondang Lor Village is efficient.